PROBLEMS AND SOLUTIONS OF ELECTRICITY QUALITY INDICATORS IN UZBEKISTAN - Kasimova Gulnoza Ravshanbekovna (Web of Journals Publishing, 2025)
This article analyzes the problems of electricity quality in Uzbekistan, in particular voltage instability. The study analyzes the weaknesses of the power system and regulatory shortcomings. The article studies successful international practices of developed countries and develops theoretical and practical solutions for improving electricity quality. Recommendations include the introduction of smart grid technologies, the integration of renewable energy sources, and the strengthening of the regulatory framework.
Keywords: Power quality, voltage stability, smart grids, renewable energy, energy system.